Ablation of the Microglial Protein DOCK2 Reduces Amyloid Burden in a Mouse Model of Alzheimer’s Disease - Cimino, Patrick J. (2013)
Alzheimer’s disease (AD) neuropathology is characterized by innate immune activation primarily through prostaglandin E2 (PGE(2)) signaling. Dedicator of cytokinesis 2 (DOCK2) is a guanyl nucleotide exchange factor expressed exclusively in microglia in the brain and is regulated by PGE(2) receptor EP2. DOCK2 modulates microglia cytokine secretion, phagocytosis, and paracrine neurotoxicity. EP2 ablation in experimental AD results in reduced oxidative damage and amyloid beta (Aβ) burden. This discovery led us to hypothesize that genetic ablation of DOCK2 would replicate the anti-Aβ effects of loss of EP2 in experimental AD. To test this hypothesis, we crossed mice that lacked DOCK2 (DOCK2−/−), were hemizygous for DOCK2 (DOCK2+/−), or that expressed two DOCK2 genes (DOCK2+/+) with APPswe-PS1Δe9 mice (a model of AD). While we found no DOCK2-dependent differences in cortex or in hippocampal microglia density or morphology in APPswe-PS1Δe9 mice, cerebral cortical and hippocampal Aβ plaque area and size were significantly reduced in 10-month-old APPswe-PS1Δe9/DOCK2−/− mice compared with APPswe-PS1Δe9/DOCK2+/+ controls. DOCK2 hemizygous APPswe-PS1Δe9 mice had intermediate Aβ plaque levels. Interestingly, soluble Aβ(42) was not significantly different among the three genotypes, suggesting the effects were mediated specifically in fibrillar Aβ. In combination with earlier cell culture results, our in vivo results presented here suggest DOCK2 contributes to Aβ plaque burden via regulation of microglial innate immune function and may represent a novel therapeutic target for AD.